First-line combination therapy of immunotherapy plus anti-angiogenic drug for thoracic SMARCA4-deficient undifferentiated tumors in AIDS: a case report and review of the literature - Wei, Xiaoling; Xing, Xiangju; Yao, Wei; Wang, Changzheng; Xiao, Yajie; Du, Xianzhi (Frontiers in Immunology, 2025)
BackgroundThoracic SMARCA4-deficient undifferentiated tumors (SMARCA4-UT) exhibit a notably aggressive phenotype, which is associated with poor patient survival outcomes. These tumors are generally resistant to conventional cytotoxic chemotherapy, thereby limiting the availability of effective treatment options.Case presentationWe describe a 69-year-old AIDS patient who initially presented with a fused, enlarged lymph node on the right clavicle and mild, unexplained pain under the right axilla that worsened with severe coughing episodes. An initial chest CT scan revealed multiple nodular and mass shadows in the mediastinum and multiple nodules in both lungs, as well as a small amount of pericardial effusion. Additionally, serum biomarkers of lung cancer were abnormal as follows: carcinoembryonic antigen (CEA) at 13.74 ng/mL, cytokeratin 19 fragment (CYFRA21-1) at 6.82 ng/mL, neuron-specific enolase (NSE) at 25.49 ng/mL, and progastrin-releasing peptide precursor (ProGRP) at 89.35 pg/mL. Subsequent pathology confirmed SMARCA4-deficient undifferentiated tumors. Considering that the weak immune status and intermediate PD-L1 level, the patient was treated with a first-line combination therapy of immunotherapy and anti-angiogenic drug instead of chemo-immunotherapy. The patient responded well to immunotherapy combining anti-angiogenic drugs and achieved an overall survival for more than 22 months.ConclusionOur study presented a rare case of thoracic SMARCA4-deficient undifferentiated tumors and AIDS, suggesting that first-line immunotherapy plus anti-angiogenic drugs as a potential therapeutic option for SMARCA4-UT patients under specific conditions.